Tanzania Economic Update : Who Wants a Job? - World Bank (Washington, DC, 2014)
This fifth economic update also examines prospects for economic prosperity in the context of rapid urbanization; in particular, how the growth of cities can be harnessed to create productive jobs for a labor force that is expected to double in the next 15 years. By 2030, Dar es Salaam will be a mega city of over 10 million people. As demonstrated by many countries in the world, cities encourage the creation and expansion of businesses by reducing distances between suppliers and customers. Can Dar es Salaam and other Tanzanian urban areas become thriving cities? Can they avoid becoming metropolis slums? Urbanization comes with significant challenges, notably in terms of increased pressure on infrastructure, housing, and service provision. The quality of the business climate in urban Tanzania will need to be improved, as most small and large entrepreneurs suffer from the uncertainty, corruption, and insecurity that characterize the business environment. This economic update argues that these challenges need to be addressed with a sense of urgency.